TRANSFORMASI PROGRAM KOMUNITAS UNTUK IKLIM DI PROVINSI RIAU - Fitri, Fitri; Hernimawati, Hernimawati; Dailaiti, Surya; Yandra, Alexsander; Sudaryanto, Sudaryanto (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
The climate village program has been transformed into a community program for climate, thereby expanding community awareness. The problem with this program is the lack of enumerator resources, welfare and budget. Therefore, it is necessary to know where the implementation has reached using Edward III's theory. The data used is primary and secondary data, qualitative descriptive analysis. As a result, the transformation of community programs for climate has been implemented but not in all locations. This program is hampered by technological mastery, economic needs have not been met and the need for private sector involvement.